Organizational Mechanism Of Management Of International Trade Operations In The Republic Of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses the mechanism of management of international trade operations in developed countries, opinion of researchers in the field of managing international trade operations over the countries. In addition, attention is paid to the factors that stimulate the organizational and economic mechanism of international trade operations management in Uzbekistan